Katerina Gogou- Yia Tin Apoktastasi Tou Mavrou - Boskoitis, Antonis (Greece, 2013)
A film portrait in black and white of Katerina Gogou, an anarchist poet and actress in the post-dictatorship era of Greece.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films